(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This community service project aimed to strengthen mosque youth competence in Islamic funeral management, a collective obligation (fardhu kifayah), through participatory, practice-based training in Tasikmalaya City. The program involved thirty participants and was conducted in five stages: preparation, theoretical briefing, demonstration, guided practice, and evaluation. Using a five-point Likert scale, the participants’ mean score improved from 3.1 (pre-test) to 4.5 (post-test), indicating significant enhancement of both knowledge and practical readiness. Qualitative reflections also revealed increased confidence, empathy, and willingness to serve the community. The program design adopted experiential-learning principles that emphasize concrete experience, reflection, and active experimentation. Local cultural and religious values were integrated to ensure contextual relevance and gender-sensitive implementation. Overall, this initiative proved effective in equipping mosque youth with the skills required for Islamic funeral management and nurturing social responsibility as future religious leaders. The model can be replicated in broader Islamic-education and community-empowerment contexts.